On the best approximations of functions defined on zero-dimensional groups - Timan, M. F. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We present a survey of results of the author, his postgraduates, and other mathematicians related to the problem of finding the best approximations of functions in the investigation of properties of spaces of functions defined on zero-dimensional compact commutative groups.